Establishing a national marine park in the South China Sea: legal framework necessity, feasibility assessment, and governance solutions for marine environmental protection - Huang, Yuwen (Frontiers in Marine Science, 2025)
Establishing a National Marine Park (NMP) in the South China Sea (SCS) plays a pivotal role in protecting marine biodiversity, mitigating ecological threats caused by human activities, and promoting sustainable development. This study evaluates the necessity and feasibility of establishing an NMP in the South China Sea from three dimensions: ecological conservation, economic benefits, and regional governance. Based on a comprehensive review of the current legislative status regarding national marine parks in China, it points out four pressing legal issues that need to be addressed for the construction of an NMP in the South China Sea. These issues include jurisdictional disputes over the waters of the South China Sea, gaps in domestic laws and regulations pertaining to marine parks, fragmented enforcement mechanisms, and the absence of specialized dispute resolution institution. The study proposes resolving these issues by initially establishing marine park pilot projects in waters without jurisdictional disputes, improving domestic specialized legislation and supporting implementation regulations, enhancing enforcement mechanisms, and establishing specialized dispute resolution institution to ensure the smooth construction and maintenance of the NMP in the South China Sea. With the formal establishment of the NMP in the South China Sea and the implementation of subsequent conservation and management measures, the marine ecosystem in the South China Sea will receive better protection, marking an important step for China in leading marine environmental governance in the region and serving as a model for practicing the concept of a “Marine Community with a Shared Future” in the South China Sea.